Having few remaining teeth is associated with a low nutrient intake and low serum albumin levels in middle-aged and older Japanese individuals: findings from the NIPPON DATA2010 - Mieko Nakamura; Toshiyuki Ojima; Tomomi Nagahata; Imako Kondo; Toshiharu Ninomiya; Katsushi Yoshita; Yusuke Arai; Takayoshi Ohkubo; Keiko Murakami; Nobuo Nishi; Yoshitaka Murakami; Naoyuki Takashima; et al. (Komiyama Printing Co. Ltd, 2019)
Abstract Background Oral health is thought to be associated with diet quality, and socioeconomic status (SES) affects both oral health and diet. The aim of this study was to investigate the association between the number of teeth and dietary intake as well as nutritional biomarker, considering the subjects' SES. Methods We conducted a cross-sectional analysis of data from 2049 individuals aged ≥ 50 years from the National Integrated Project for Prospective Observation of Non-communicable Disease and its Trends in the Aged 2010. The number of remaining teeth was categorized into age-specific quartiles (Q1 to Q4). We assessed the adjusted means and 95% confidence intervals for dietary variables by the number of teeth using analysis of covariance. Stratified analyses by SES were also conducted. Results The intake of grain products was 31 g higher, and those of vegetables and meat were 30 g and 8 g lower, respectively, in Q1 (fewer teeth) than in Q4 (more teeth). Carbohydrate intake was higher whereas protein, minerals (potassium, magnesium, and zinc), vitamins (vitamins A, E, B1, B6, β-carotene, and folic acid), and dietary fiber intakes were lower among individuals with fewer teeth. Adjusted mean serum albumin levels were low in Q1. The associations between the number of teeth and dietary intake were more evident in individuals with a low SES. Conclusions Having few remaining teeth was associated with a low nutrient intake and low serum albumin levels in middle-aged and older Japanese adults, and these associations were more evident in individuals with low SES.